Critical questions for Facebook's virtual reality: Data, power and the metaverse - Ben Egliston; Marcus Carter (Internet Policy Review, 2021)
Virtual Reality (VR) represents an emerging class of spatial computing technology reliant upon the capture and processing of data about the user (such as their body and its interface with the hardware), or their surrounding environment. Much like digital media more generally, there are growing concerns of who stands to benefit from VR as a data-intensive form of technology, and where its potential data-borne harms may lie. Drawing from critical data studies, we examine the case of Facebook's Oculus VR-a market leading VR technology, central to their metaverse ambitions. Through this case, we argue that VR as a data-intensive device is not one of unalloyed benefit, but one fraught with power inequity-one that has the potential to exacerbate wealth inequity, institute algorithmic bias, and bring about new forms of digital exclusion. We contend that policy to date has had limited engagement with VR, and that regulatory intervention will be needed as VR becomes more widely adopted in society.
Keywords: 300; Virtual reality; Critical Data Studies; Sensors; Power; Data; Social media